PENINGKATAN KAPASITAS PENENUN CORAK INSANG MELALUI PELATIHAN MOTIVASI USAHA DAN MENGANIK - Husna Amalya Melati; Yudithya Ratih; Metasari Kartika (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2017)
Non Government Organisations as known as Kelompok Swadaya Masyarakat (KSM) Mekar IIand Pucuk Rebung became the only Insang style of weaving craft employers in the city ofPontianak were located on Jalan Khatulistiwa, Batulayang District. The Insang style of weavingis one of the features produced by KSM, besides the typical weaving of Sambas. Only a smallportion of craft employers or weavers which produces the weaving of Insang style because it isfeared that the market target is not much, however this pattern is a typical of Pontianak city;The capital of West Kalimantan Province. Decreased motivation for weaving since it faced theproblem not knowing how to understand that is the upstream process in weaving. Training isdone by giving the material about the weaving process, especially the stage of understandingand motivation and business development opportunities to the partners until all the materialpresented and implemented. Participants said that they were ready to weave back and werewilling to support the development of their area into a village or a weaving center. One of themis shown by the willingness of their house to be decorated or painted with Insang style. Thetraining that was done successfully resulted in more than 15 people weavers who haveunderstood how to do the â€œnganikâ€ process.